GENESIS AND CONCEPTUAL FOUNDATIONS OF MUSLIM LAW - Alona O. Taranovska (Alfred Nobel University Journal of Law)
The article is devoted to the problem of defining the conceptual foundations of Muslim law, inherent in its characteristic features. Emphasize the importance of studying the theological ideas of Islam, as they permeate legal concepts, forming a different "vision" of legal phenomena and legal reality. Attention is drawn to the relevance of scientific knowledge of Islamic religious doctrine in the conditions of modern trends, as a powerful ideological vector of the development of Muslim law, regardless of the inherent conservatism of Islamic society. In addition, the idea of the dualistic nature of Muslim law and its multifaceted nature is asserted, which is based on the conclusions of prominent legal scholars and religious scholars of the past and present, such as Abu Hanif, A. Ibn Khaldun, J. Schacht and others. The article presents the conclusions of the well-known modern scientist Benjamin Jokish regarding the borrowing of legal ideas of Jewish law, Roman law and Byzantium by theorists of Muslim law. The author, in general terms, reveals the issue of the genesis of Muslim law, in particular, the periodization of Muslim law is mentioned as a generalization of the historical stages of its existence, the role of legal schools (madhabs) in the process of the development of Muslim law is noted. The issue of distinguishing between the concepts of "Sharia" and "Fiqh" is also highlighted separately, attention is appropriately paid to the changing role of these two categories in the theory of Muslim law, since, first of all, the subject field of Fiqh began where the field of Sharia ended, which later acquired a different meaning. The field of research on the sources of Muslim law does not lose its relevance, in addition to the Qur'an and the Sunnah, the knowledge of the meaningful essence of ijtihad as a source of Muslim law derived from the Qur'an and the Sunnah, which is a functional tool for solving controversial issues of human existence and social life in general, acquires special importance.